2016
DOI: 10.1371/journal.pone.0159983
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Inhibition of NFAT5-Mediated Induction of CCL2 in Hyperosmotic Conditions by Cyclosporine and Dexamethasone on Human HeLa-Modified Conjunctiva-Derived Cells

Abstract: PurposeTo investigate the pro-inflammatory intracellular mechanisms induced by an in vitro model of dry eye disease (DED) on a Hela-modified conjunctiva-derived cells in hyperosmolarity (HO) stress conditions. This study focused on CCL2 induction and explored the implications of the nuclear factor of activated T-cells 5 (NFAT5) as well as mitogen-activated protein kinases (MAPK) and nuclear factor kappa B (NFĸB). This work was completed by an analysis of the effects of cyclosporine A (CsA), dexamethasone (Dex)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 66 publications
4
13
0
Order By: Relevance
“…However, additional HO stress probably broke down the negative loop regulation leading to a significant increase in their expression. HO also slightly increased the expression NFκB, a protein complex that controls transcription of DNA, cytokine production, and cell survival, in accordance with previous studies where NFκB was reported to have a role in HO-induced cellular signaling [38,75]. In HCE, the observed mRNA up-regulation of SOD1, one of the main antioxidant enzymes [57,76], meaning a setting-up of cellular defense system, even better adjusted under HO hormetic effect.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…However, additional HO stress probably broke down the negative loop regulation leading to a significant increase in their expression. HO also slightly increased the expression NFκB, a protein complex that controls transcription of DNA, cytokine production, and cell survival, in accordance with previous studies where NFκB was reported to have a role in HO-induced cellular signaling [38,75]. In HCE, the observed mRNA up-regulation of SOD1, one of the main antioxidant enzymes [57,76], meaning a setting-up of cellular defense system, even better adjusted under HO hormetic effect.…”
Section: Discussionsupporting
confidence: 91%
“…The measured osmolarity values were within the range of the hyperosmolarity commonly used in experimental settings (e.g. [38,45],). For both cell types, we decided to keep the same composition of culture media, in order not to induce an additional stress and to be able to assess the specific phototoxic effect.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations